Analysis of the Need for Using the Independent Teaching Platform to Improve Teacher Performance in Schools - Sri Sudarsih (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
This research aims to analyze teachers' needs for the use of the Merdeka Mengajar Platform (PMM) in the context of implementing the Independent Curriculum. The research method in this research uses quantitative descriptive analysis techniques. The data collection technique uses a needs questionnaire which is distributed directly to teachers. The population of this study were teachers in the MGMP English community at the junior high school level in Bengkulu City. In this research, the technique of distributing questionnaire sheets filled out by teachers was used to determine the level of teachers' needs for PMM applications in learning. The data analysis technique in this research uses quantitative techniques and is concluded quantitatively. From 36 respondents, data was obtained that 25% of teachers were still not familiar with PMM, only 14 teachers used PMM in learning. 58.3% of teachers stated that there was a need for training in using PMM in learning and recommended the use of PMM to other fellow teachers. Based on the results of data analysis, it is concluded that there is a need for socialization and training on the use of PMM for all teachers so that the implementation of the Independent Curriculum can run well and teacher performance and competence can increase.